Manajemen Pembelajaran PAI Berbasis Proyek di SMP Muhammadiyah 2 - Ayu Faradillah; Istikomah Istikomah (Dinasti Research, 2024)
Project-based Islamic religious education learning management is an approach that integrates learning management concepts with the project methods in the learning process. This research aims to identify, and analyses project based PAI learning management and their impact on students’ understanding of Islamic religious concepts and critical thinking skills. The research method used is qualitative research with a case study approach at SMP Muhammadiyah 2 Taman. Data was collected through observation, interviews with teachers. The research result show that PAI learning management involves careful planning, interactive implementation, and continuous evaluation. The teacher acts as a facilitator who encourages students’ active participation in learning projects. The impact of eliminating project based PAI learning management can be seen in increasing understanding of Islamic religious concepts and developing students’ critical thinking skills. Learning projects integrate theory with practice, allowing students to relate Islamic religious teachings to context of everyday life. Apart from that, students also develop critical thinking skills through problem solving.